ChemInform Abstract: Regioselective Synthesis of Elusive 4, 9‐Dihydro‐1H‐carbazoles by Gold‐Catalyzed Cycloisomerization of 3‐Allenylmethylindoles. Issue 9 (4th March 2014) - Alvarez, Estela; Garcia‐Garcia, Patricia; Fernandez‐Rodriguez, Manuel A.; Sanz, Roberto
Abstract A general and efficient synthesis of carbazoles from 3‐allenylmethylindoles is reported.